2021
DOI: 10.48550/arxiv.2112.06396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does Fully Homomorphic Encryption Need Compute Acceleration?

Abstract: The emergence of cloud-computing has raised important privacy questions about the data that users share with remote servers. While data in transit is protected using standard techniques like Transport Layer Security (TLS), most cloud providers have unrestricted plaintext access to user data at the endpoint. Fully Homomorphic Encryption (FHE) offers one solution to this problem by allowing for arbitrarily complex computations on encrypted data without ever needing to decrypt it. Unfortunately, all known impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(70 reference statements)
0
7
0
Order By: Relevance
“…In contrast, prior FHE processors that supported bootstrapping of second-generation schemes were often bottlenecked by the required memory bandwidth [37,52]. In fact, a recent architectural analysis of bootstrapping [16] found that it exhibits low arithmetic intensity and requires large caches. Their conclusion was that FHE processors only benefit marginally from bespoke high-throughput arithmetic units.…”
Section: Batch Bootstrappingmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, prior FHE processors that supported bootstrapping of second-generation schemes were often bottlenecked by the required memory bandwidth [37,52]. In fact, a recent architectural analysis of bootstrapping [16] found that it exhibits low arithmetic intensity and requires large caches. Their conclusion was that FHE processors only benefit marginally from bespoke high-throughput arithmetic units.…”
Section: Batch Bootstrappingmentioning
confidence: 99%
“…These schemes require bootstrapping only after a certain number of operations. For these schemes, bootstrapping is a complex algorithm that requires large data caches [16] and exhibits low arithmetic intensity, and essentially all prior architectures that support bootstrapping have hit the off-chip memory-bandwidth wall [37,52].…”
Section: Introductionmentioning
confidence: 99%
“…Prior work has identified that HE ops have very low arithmetic intensity and are bounded by off-chip memory bandwidth [26], [45], [72]. Even a simple HE op, such as HMult, has a working set including several ciphertexts and an evk, which amounts to several hundreds of MBs.…”
Section: A Limitations Of Prior He Acceleratorsmentioning
confidence: 99%
“…BACKGROUND We explain the pertinent details of HE with an emphasis on CKKS. We adopt notations and terminologies from [26], [34]. Parameters and notations are summarized in Table I.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, a recent study by De Castro et al highlighted the memory bottleneck of FHE acceleration [15]. The starting point for their analysis is a CPU-like architecture, where ciphertexts do not fit in the Last-Level Cache (LLC).…”
Section: Related Workmentioning
confidence: 99%